Saccharomyces cerevisiae may serve as a probiotic in colorectal cancer by promoting cancer cell apoptosis. Issue 10 (29th September 2020) - Li, Jia Qi; Li, Jia Lu; Xie, Yuan Hong; Wang, Yao; Shen, Xiao Nan; Qian, Yun; Han, Ji Xuan; Chen, Ying Xuan; Fang, Jing‐Yuan
Abstract : Objectives: Shotgun metagenomic sequencing of human fecal samples has shown that Saccharomyces cerevisiae ( S. cerevisiae ) is significantly suppressed in colorectal cancer (CRC) and probably plays an important role in CRC progression. However, these results need to be validated. Here we aimed to confirm the results of high‐throughput sequencing and demonstrate the mechanisms mediating the effect of S. cerevisiae on progression from colorectal adenoma (CRA) to CRC. Methods: We used a quantitative polymerase chain reaction (qPCR) assay to examine the relative abundance of S. cerevisiae in 281 fecal samples collected from 106 healthy controls, 108 patients with CRA and 67 with CRC. C57BL/6 and APC Min/+ mouse models and in vitro cell assays were subsequntly used for additional analyses. The mouse models were treated or not treated with broad‐spectrum antibiotics and given an S. cerevisiae gavage for 8 weeks. Western blot, 16S rRNA sequencing, qPCR, immunohistochemistry, RNA sequencing, cell counting kit‐8 assay, colony formation assay and flow cytometry were performed. Results: S. cerevisiae was 2.68‐fold and 3.94‐fold less abundant in patients with CRA and CRC, respectively, than in the controls. In vivo experiments showed that S. cerevisiae reduced colorectal tumor progression by promoting epithelial cell apoptosis and modulated gut microbial structure and intestinal immunity. S. cerevisiae downregulated nuclear factor kappa light chain enhancer of activated B cells and the mechanistic target of rapamycin signaling pathways. Cell assays confirmed the pro‐apoptotic effect of S. cerevisiae . Conclusions: S. cerevisiae may play a probiotic role in CRC by promoting cancer cell apoptosis. It can reduce CRC progression by modulating the mucosal microbial structure. Abstract : Decreased Saccharomyces cerevisiae may inhibit colorectal cancer progression by modulating intestinal immunity and microbiota and enhancing cell apoptosis.